(2√3-3√2)(2√3+3√2)=
(-√11+t)(√11+t)=
Răspunsuri la întrebare
Răspuns de
0
12-18=(t-√11)(t+√11)=t²-11
-6=t²-11
-6+11=t²
5=t²
t²=5
t∈{-√5;√5}
-6=t²-11
-6+11=t²
5=t²
t²=5
t∈{-√5;√5}
Răspuns de
1
regula calculului prescurat
(a+b)(a-b)=a²-b²
1)(2√3)²-(3√2)²=4*3-9*2=12-18=-6
2)(-√11+t)(√11+t)=(t-√11)(t+√11)=t²-√11²=t²-11
(a+b)(a-b)=a²-b²
1)(2√3)²-(3√2)²=4*3-9*2=12-18=-6
2)(-√11+t)(√11+t)=(t-√11)(t+√11)=t²-√11²=t²-11
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă